Prosthetic rehabilitation of edentulism prevents malnutrition in nursing home residents - Zenthöfer, Andreas; Rammelsberg, Peter; Cabrera, Tomas; Hassel, Alexander J. (The international journal of prosthodontics, 2015)
To investigate the association between prosthetic rehabilitation and malnutrition in institutionalized elders, 255 nursing home residents were recruited for this study and underwent a comprehensive dental examination. The body mass index (BMI) was administered to estimate the nutritional condition. Participants with BMI < 20 kg/mc were categorized as malnourished (n = 33), whereas all others were categorized as adequately nourished (n = 222). The number of teeth present and the prevalence of prosthetic rehabilitation were significantly lower in malnourished participants (P < .05). Malnutrition risk was 4.6 times higher for participants who were edentulous and did not wear dentures. Adequate replacement of teeth is important to prevent malnutrition in institutionalized older people.
Gesehen am 23.07.2020